Is the city the appropriate scale for participatory democracy? Some answers from Brazil - Legard, Sveinung (Politik, 2016)
This study compares participatory budgeting at the city and state level in Brazil. It shows that, that even though the practice of participatory budgeting more closely resembles the ideals of participatory democracy at the city level, this does not mean that participatory democracy is impossible at larger scales. To the contrary, the difference between participatory budgeting at the city and state level is more a question of gradations than vast leaps of democratic merit. Furthermore, some of the features that are considered unique to the city – neighborhood-based community associations that mobilize and discuss with citizens in local public spheres – are also important in participatory budgeting at the state level. The experiences of participatory budgeting at the city and state level in Brazil suggest that it is wrong to overemphasize the uniqueness of the city and also to undervalue the special role the city might play in larger participatory processes.